Academic obituaries: analysis of posthumous tributes of science in scientific journals - Hayashi, Maria Cristina Piumbato Innocentini (2021)
Obituaries have been studied in the literary, journalistic and sociological fields through analyzes that point to issues related to social markers of gender, class, ethnicity and age differences. However, studies that analyze academic obituaries published in scientific journals are still scarce in the area of Information Science, and in Brazil almost nonexistent. In order to fill this gap, this article sought to answer the following questions: which categories should comprise a model of analysis of academic obituaries, and how are they characterized when they are published in Brazilian scientific journals? Theoretically the study is anchored in the fields of Information Science and Sociology of Science. As a methodological resource, bibliometric and content analyzes were used. The analysis model was composed of a set of indicators based on revealing categories of the profiles of the journal, the obituary, the person deceased and the obituarist as well as the academic and personal attributes, values and virtues of the deceased academics. The analysis model was applied to academic obituaries (n = 309) from eight areas of knowledge published between 2009 and 2019 in journals (n = 94) in the SciELO eletronic library. The results showed the innumerous particularities of the life and work of the persons deceased, offering a revealing portrait of what is valued by the academic community and area of knowledge in which they are inscribed.